For Gods, Ghosts and Ancestors : The Chinese Tradition of Paper Offerings - Scott, Janet Lee, 1945- (Royal Asiatic Society Hong Kong studies series., 2007)
Throughout For Gods, Ghosts and Ancestors, paper offerings are presented as a vibrant and living tradition expressing worshippers' respect and gratitude for the gods, as well as love and concern for departed family members.